Increasing understanding of general knowledge of plastics with video-based learning - Nashar, Norfatin Afiqah; Jumintono, Jumintono; Pudyastuti, Rita Rena; Etty Handayani, Etty Handayani; Indarto, Muhammad Roni; Jaka Sunardi, Jaka Sunardi; Retnowati, Nurcahyani Dewi; Sawitri, Sicilia (Horizon Research Publishing, 2020)
This study was motivated by video-based learning materials on general knowledge, which is getting more popular. In many cases, video-based education is one of the best ways to learn in today's digital technology. The purpose of this study is to explore the increasing student understanding of learning general knowledge about plastics. This research was conducted using fundamental quantitative analysis in a video tutorial involving 28 respondents from polymer technology students at Mara University Technology (UiTM). The data were collected by giving tests to students before (pre-test) and after (post-test) watching the video. There are five questions students must answer. Data were collected and analysed using the Statistical Package for Science for Windows software Version 21.0 (SPSS V21.0). The frequency and percentage are re-coded to compare the results between pre-test and post-test. A positive response means an increase in the ratio and the percentage of students who get the correct answer on the post-test. This treatment shows a positive response to video-based learning from students. The study results concluded that there was a significant increase compared to before and after the test. Instructional videos make the learning environment more attractive than textbook learning. In this way, learning can provide many benefits for students and teaching staff in increasing their understanding of general knowledge about plastics.